The Trap Technique. - Stick, D.
A full-scale quantum computer would work like the standard desktop computer, in that it would have a place to store data, a place where a program manipulates the data, and interconnections to move the data from one to the other. In the computer you are using now, bits of data - stored as quantity of charge or its absence - are transferred from memory to a processor in the form of levels of voltage. At the processor the computer's program determines which logic operations the bits will be subjected to. Once the logic operations are completed, the bits are converted to amounts of charge and stored in memory again. Similarly, in an ion-trap computer, stored qubits would be called from a storage trap to a logic trap, the kind we've been building so far. The two traps would be connected by a long trap that acts like an interconnect or a data bus. It sounds simple, but such a structure would have to be repeated and connected many dozens of times on the same chip to handle the number of ions we'd need. Therefore, a quantum computer equivalent of very-large-scale integration would be required to handle the control circuitry just to move the ions around. The small-scale quantum algorithms that scientists are running today and plan to run in the near future will almost certainly lead to insights that could make full-scale quantum computing, if not easy, at least more tractable.
Keywords: Data bus; Full-scale quantum computer; Ion trap technique; Logic operation